Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
2x + 5y = -3 ⇒ 2x + 5y = -3
1x + 8y = 4 ⇒ 2x + 16y = 8
-11y = -11
-11 -11
y = 1
2x + 5(1) = -3
2x + 5 = -3
-5 -5
2x = -8
2 2
x = -4
(x, y) = (-4, 1)
2x + 1y = 7 ⇒ 2x + 1y = 7
1x - 2y = -14 ⇒ 2x - 4y = -28
5y = 35
5 5
y = 7
2x + 7 = 7
-7 -7
2x = 0
2 2
x = 0
(x, y) = (0, 7)
1x + 8y = 4 ⇒ 2x + 16y = 8
-11y = -11
-11 -11
y = 1
2x + 5(1) = -3
2x + 5 = -3
-5 -5
2x = -8
2 2
x = -4
(x, y) = (-4, 1)
2x + 1y = 7 ⇒ 2x + 1y = 7
1x - 2y = -14 ⇒ 2x - 4y = -28
5y = 35
5 5
y = 7
2x + 7 = 7
-7 -7
2x = 0
2 2
x = 0
(x, y) = (0, 7)
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.